Effect of Sources and Levels of Phosphorus and P Solubilizers on iYield and Nutrient Uptake in Rainfed Greengram - Duraisami, V P; Mani, A K; Thilagavathi, T (Annals of Arid Zone, 2016)
Grain and haulms yield, nutrient uptake, nutrient use efficiency (NUE) and recovery were improved by the sources of P in greengram. The single super phosphate (SSP) @ 18.75 kg P20S ha'i coupled with seed soaking registered higher yield, Puptake and SIC ratio. The rock phosphate (RP) @ 25 kg P20S ha'i with phosphobacterium and VA-Mycorrhiza was at par with SSP. The net gain in P balance was higher under integration of RP with P solubilizing microorganisms as compared to SSP treatments.